65.4: Speckle Suppression by Limited Phase Range in Laser Projection Systems. Issue 1 (1st July 2013) - Chang, Yan‐Shuo; Lin, Chia Hsin; Hsu, Ku‐Hui; Lin, Hoang Yan
Abstract Speckle contrast of speckled images can be reduced by a limited range of phase of the incident field. We designed novel diffractive optical elements for beam shaping and phase limitation for a coherent projection display. By cooperating with a second element, the speckle contrast was reduced from 1.0033 to 0.1658.